Applied anthropology in Canada : understanding Aboriginal issues - Hedican, Edward J. (University of Toronto Press, 2008)
"In this second edition of a classic in the field, Edward Hedican takes stock of anthropology's research on current indigenous affairs and offers an up-to-date assessment of Aboriginal issues in Canada from the perspective of applied anthropology. In this central thesis Hedican underlines the opportunity of anthropology to make a significant impact on the way Aboriginal issues are studied, perceived, and interpreted in Canada. He contends that anthropologists must stop lingering on the periphery of debates concerning land claims and race relations and become more actively committed to the public good. His study ranges over such challenging topics as advocacy roles in Aboriginal studies, the ethics of applied research, policy issues in community development, the political context of the self-government debate, and the dilemma of Aboriginal status and identity in Canada" "This book is an impassioned call for a revitalized anthropology - one more directly attuned to the practical problems faced by First Nations peoples. Hedican's focus on Aboriginal issues gives his work a strong contemporary relevance that bridges the scholarly and the public spheres."--Jacket.